1984
DOI: 10.1111/j.1365-2591.1984.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fluoride release from three glass ionomer cements and a polycarboxylate cement

Abstract: Abstract. This study investigated the fluoride release from three glass ionomer cements, ASPA, ChemFil and ChemBond, and a fluoride‐enriched polycarboxylate cement, Poly‐F Plus, using a simulated model cavity system. ChemFil released considerably more fluoride than the other materials at all the time intervals investigated. The release from ASPA was greater than that for either ChemBond or Poly‐F Plus. Release from ChemFil and ASPA was of a similar order to a silicate cement investigated previously and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
4

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 21 publications
3
12
0
4
Order By: Relevance
“…The high release o f fluoride obtained in the first 24 h is in agreement with previous studies [Crisp et al, 1980: Mcryon andSmith. 1984;HI Mallakh and Sarkar, 1990], The level of release dropped rapidly after 48 h and had almost plateaued by the 10th day.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The high release o f fluoride obtained in the first 24 h is in agreement with previous studies [Crisp et al, 1980: Mcryon andSmith. 1984;HI Mallakh and Sarkar, 1990], The level of release dropped rapidly after 48 h and had almost plateaued by the 10th day.…”
Section: Discussionsupporting
confidence: 82%
“…Although these materials have inferior mechanical proper ties to other restorative materials, their use is being advocat ed because of their potential anticaries benefits to the ad jacent dental hard tissues. Many in vitro studies [Meryon andSmith, 1984: Wilson ct ah. 1985;HI Mallakh and Sarkar, 1990] have shown that fluoride is released from these mate rials with the maximum fluoride release within the 1st day immediately following setting of the material, falling to a plateau after several weeks.…”
mentioning
confidence: 99%
“…In addition, Meryon and Smith 38) concluded that fluoride released from GIC is not from the GIC core but rather from the matrix. In our study, XPS analysis showed that fluorine contents in the matrices of the A100-and A100f-GICs were higher than in the matrix of the A200-GIC, and that the fluorine content of the A200-GIC was lower than that of the control-GIC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, careful oral hygiene and a fluoride preventive program are recommended. Glass ionomer cements release fluoride to saliva and surrounding tooth structures [Swartz et al, 1980[Swartz et al, , 1984Meryon and Smith, 1984;Retief et al, 1984], Used as an alternative to composite for cementation of bands and brackets, glass ionomer cement acts as a slow-release system for fluoride. An advantage might be that the released fluoride then exerts a local cariostatic effect at the sites where the caries challenge is •ncreased during orthodontic treatment.…”
mentioning
confidence: 99%